Analysis of nutrition research networks in West Africa: Application of social network analysis to co-authorship data to understand and enhance collaboration - Aberman, Noora-Lisa; Diop, Loty; Verstraeten, Roosmarijn (International Food Policy Research Institute, 2021)
Despite limited progress to date, we now see a growing political commitment to addressing the high rates of maternal and child undernutrition in West Africa. Such commitment needs to be effectively translated into appropriate choices and effective program action in order to generate large-scale, sustained change.